2014
DOI: 10.1371/journal.pone.0102168
|View full text |Cite
|
Sign up to set email alerts
|

Size Selection of Antarctic Krill (Euphausia superba) in Trawls

Abstract: Trawlers involved in the Antarctic krill (Euphausia superba) fishery use different trawl designs, and very little is known about the size selectivity of the various gears. Size selectivity quantifies a given trawl's ability to catch different sizes of a harvested entity, and this information is crucial for the management of a sustainable fishery. We established a morphological description of krill and used it in a mathematical model (FISHSELECT) to predict the selective potential of diamond meshes measuring 5–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 11 publications
(27 reference statements)
2
68
0
Order By: Relevance
“…These spatial and temporal scales were chosen to range from the scale of a typical net tow by a fishing vessel or foraging trip of a penguin up to annual overlap on proposed fishery management units. For example, a 0.25° longitude by 0.125° latitude grid, equivalent to a 13 km by 14 km polygon at 62°S, is similar to the average maximum distances from tagging locations achieved during summer foraging trips by penguins (19.4 ± 9.75 km) and the average lengths of tows reported by fishing vessels (1.4 ± 0.6 hr, equivalent to 7.8 ± 3.5 km), assuming maximum towing speeds of 3 knots [51]. …”
Section: Methodssupporting
confidence: 56%
“…These spatial and temporal scales were chosen to range from the scale of a typical net tow by a fishing vessel or foraging trip of a penguin up to annual overlap on proposed fishery management units. For example, a 0.25° longitude by 0.125° latitude grid, equivalent to a 13 km by 14 km polygon at 62°S, is similar to the average maximum distances from tagging locations achieved during summer foraging trips by penguins (19.4 ± 9.75 km) and the average lengths of tows reported by fishing vessels (1.4 ± 0.6 hr, equivalent to 7.8 ± 3.5 km), assuming maximum towing speeds of 3 knots [51]. …”
Section: Methodssupporting
confidence: 56%
“…Further elimination of results that are probably influenced by large differences in environmental factors (natural environment vs. experimental) and exposure to rough physical conditions during the catching process, suggest that haul 4 was the most benign and that the true mortality range is, at most between 1% and 6%. In Krag et al (2014) an L50 value (50% retention length) for krill was estimated at 32.72 mm for the commercially used 16 mm mesh size, similar to the mesh used in this experiment. This would mean that individuals larger than 33 mm that manage to escape will experience increased mechanical contact with the mesh as they pass through it, such that we could expect large individuals to show the highest mortality rate.…”
Section: Discussionmentioning
confidence: 95%
“…It is highly likely that differences in applied fishing technologies will influence differently the degree of escapement and escape mortality. Mathematical modelling techniques and practical experiments on size selection of krill have suggested that krill can escape from some of the smallest commercial meshes used in the fishery (Krag et al, 2014). However, information on the mortality of escaped krill in the primary scientific literature is virtually non-existent.…”
Section: Introductionmentioning
confidence: 99%
“…The sequence of analysis described above was implemented in the SELNET software tool , which was used for all analyses. SELNET has previously been applied to analyze size-selectivity data (Sistiaga et al 2010;Frandsen et al 2011;Wienbeck et al 2011Wienbeck et al , 2014Eigaard et al 2012;Herrmann et al 2012Herrmann et al , 2013aHerrmann et al , 2013bHerrmann et al , 2013cHerrmann et al , 2013dHerrmann et al , 2015Madsen et al 2012;Krag et al 2014a;Tokac et al 2014;Sala et al 2015) and catch comparison data (Krag et al 2014b) collected with trawls. This is the first time this method was used to analyze catch data of fishing gears such as boat seines and surrounding nets.…”
Section: Catch Performance Of a Surrounding Netmentioning
confidence: 99%